Ministerial bureaucracies as stand-in agenda setters? A comparative description - Kai-Uwe Schnapp (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
This paper sets out to theoretically conceptualise and empirically describe the potential ability of ministerial bureaucracies to influence policy-making. The theoretical framework describes the chances for bureaucracies to influence policymaking as accruing from three sources: the organisational structures of the bureaucracy itself, room for bureaucratic discretion resulting from the preference configurations of the political actors, and the chance for the bureaucracy to act as political agenda setter rather than politicians. A quantitative empirical description of 21 OECD-countries is presented with the aim of comparing the relative strengths of the national ministerial bureaucracies. The paper concludes with an empirical classification of administrative systems. Japan, Belgium, and Ireland are found to be countries with a strong position for the bureaucracy in all of the theoretically described dimensions. The opposite end of the spectrum is marked by New Zealand, where the bureaucracy appears to be comparatively weak. – – In dieser Arbeit wird versucht, die Möglichkeiten von Ministerialverwaltungen zur Beeinflussung politischer Entscheidungsprozesse theoretisch zu fassen und anschließend quantitativ zu beschreiben. Das theoretische Konzept beschreibt den Einfluss von Bürokratien als aus drei Quellen kommend: den Organisationsstrukturen der Bürokratie selbst, dem Entscheidungsspielraum, der ihr als Folge bestimmter Präferenzkonstellationen der politischen Akteure erwächst, sowie der Möglichkeit der Bürokratie, unter bestimmten Umständen die Setzung der politischen Tagesordnung anstelle der politischen Akteure zu übernehmen. Mit dem Ziel eines Vergleichs der relativen Einflussposition ihrer nationalen Ministerialbürokratien wird eine quantitative Beschreibung der Ministerialverwaltungssysteme von 21 OECD-Ländern geliefert. Die Arbeit schließt mit einer empirischen Klassifikation von Verwaltungssystemen. Japan, Belgien und Irland werden als Länder beschrieben, in denen die Ministerialbürokratie auf allen drei theoretisch etablierten Dimensionen relativ einflussstark ist. Das andere Ende des Einflussspektrums wird von Neuseeland mit einer vergleichsweise schwachen Bürokratie eingenommen.
Keywords: 300